Strategies To Improve Business Performance In The Face Of Strong Competition - Shofwani, Siti Aniqoh; Misidawati, Dwi Novaria; Turyandi, Itto; Arwin, Arwin; Ansari, Ansari (Yayasan Riset dan Pengembangan Intelektual, 2024)
Jakarta Cosmetics Store is one of the stores engaged in the sale of various cosmetic products and various skincare products. The number of competitors in the cosmetics sector, such as Jakarta Cosmetics Store, requires the right marketing strategy to be able to face the competition in the cosmetics market. The purpose of the study was to determine the strategy implemented by the company to improve its business performance. The research informants numbered 8 people. The method used in this study was the descriptive method. The use of the descriptive method is to determine the application of SWOT analysis in determining strategies to improve its business performance. The results of the study indicate that Jakarta Cosmetics Store must take advantage of opportunities as much as possible, by using an aggressive strategy to be able to attack the market and can widen the gap in competition.